Prevalensi dan Pola Peresepan Obat Asma Eksaserbasi pada Salah Satu Rumah Sakit Di Klaten - Sutaryono; Rahmi Nurhaini; Fahmiya khusnul khotimah (MOTORIK Jurnal Ilmu Kesehatan, 2019)
Exacerbation of asthma is a condition of worsening asthma symptoms that result in disruption of one's activities. Treatment efforts that are not in accordance with the guidline actually worsen and have side effects. This study aims to determine the prevalence and characteristics of exacerbation of asthma drugs given by doctors. The study design used retrospective data on 82 exacerbated asthma patients in the outpatient pharmacy Dr. Soeradji Tirtonegoro Klaten in 2018. The results showed the prevalence of asthma exacerbations of 461 cases. The drug groups obtained included beta-2 agonists (41.4%), corticosteroid groups (30.4%), antihistamines (16%), mucolytic groups (6.1%), analgesic groups (6.1%) . The types of drugs that are often used are salbutamol (39.0%), methylprednisolone (17.1%), seretide (10.9%), cetirizine (10.9%), ambroxol (6.1%), paracetamol (6, 1%), ranitidine (4.9%), simbicort (2.5%), dexametasone (2.5%). The results showed that the drugs most prescribed by doctors were the Beta-2 Agonist drugs with salbutamol.